Exosomal miR-125b-5p derived from adipose-derived mesenchymal stem cells enhance diabetic hindlimb ischemia repair via targeting alkaline ceramidase 2 - Guo, Jiahe; Yang, Xiaofan; Chen, Jing; Wang, Cheng; Sun, Yue; Yan, Chengqi; Ren, Sen; Xiong, Hewei; Xiang, Kaituo; Zhang, Maojie; Li, Chengcheng; Jiang, Guoyong; et al. (Journal of nanobiotechnology, 2023)
Ischemic diseases caused by diabetes continue to pose a major health challenge and effective treatments are in high demand. Mesenchymal stem cells (MSCs) derived exosomes have aroused broad attention as a cell-free treatment for ischemic diseases. However, the efficacy of exosomes from adipose-derived mesenchymal stem cells (ADSC-Exos) in treating diabetic lower limb ischemic injury remains unclear. Exosomes were isolated from ADSCs culture supernatants by differential ultracentrifugation and their effect on C2C12 cells and HUVECs was assessed by EdU, Transwell, and in vitro tube formation assays separately. The recovery of limb function after ADSC-Exos treatment was evaluated by Laser-Doppler perfusion imaging, limb function score, and histological analysis. Subsequently, miRNA sequencing and rescue experiments were performed to figure out the responsible miRNA for the protective role of ADSC-Exos on diabetic hindlimb ischemic injury. Finally, the direct target of miRNA in C2C12 cells was confirmed by bioinformatic analysis and dual-luciferase report gene assay. ADSC-Exos have the potential to promote proliferation and migration of C2C12 cells and to promote HUVECs angiogenesis. In vivo experiments have shown that ADSC-Exos can protect ischemic skeletal muscle, promote the repair of muscle injury, and accelerate vascular regeneration. Combined with bioinformatics analysis, miR-125b-5p may be a key molecule in this process. Transfer of miR-125b-5p into C2C12 cells was able to promote cell proliferation and migration by suppressing ACER2 overexpression. The findings revealed that miR-125b-5p derived from ADSC-Exos may play a critical role in ischemic muscle reparation by targeting ACER2. In conclusion, our study may provide new insights into the potential of ADSC-Exos as a treatment option for diabetic lower limb ischemia.